Skin and Its Regenerative Powers: An Alliance between Stem Cells and Their Niche - Uy Gonzales, Kevin Andrew (Dev Cell, 2017)
Tissues have a natural capacity to replace dying cells and to heal wounds. This ability resides in resident stem cells, which self-renew, preserve, and repair their tissue during homeostasis and following injury. The skin epidermis and its appendages are subjected to daily assaults from the external environment. A high demand is placed on renewal and regeneration of the skin’s barrier in order to protect the body from infection and dehydration and to heal wounds. This review focuses on the epithelial stem cells of skin, where they come from, where they reside, and how they function in normal homeostasis and wound repair.